Towards understanding the distribution and tumor targeting of sericin regulated spherical calcium phosphate nanoparticles. Issue 3 (17th November 2016) - Zhao, Ruibo; Ren, Xiaoyuan; Xie, Chungang; Kong, Xiangdong
Abstract: The study of calcium phosphate (CaP) nanoparticles in vivo is still incomplete, which has limited their applications for biomedical delivery. Herein, we synthesized amorphous spherical calcium phosphate (S‐CaP) nanoparticles with an average size of 80 nm via a co‐precipitation method in the presence of silk sericin as the regulation template. S‐CaP was labeled by the near‐infrared dye reagent DiR, and then, the labeled nanoparticles (S‐CaP@DiR) were used to investigate the distribution and degradation in healthy mice by IVIS and TEM. The results showed that the S‐CaP nanoparticles were mainly distributed in the liver, and ∼90% of them (500 μg) could be degraded by the liver within 2 weeks. Tumor‐bearing mice were then prepared, and the S‐CaP was injected intravenously. Strikingly, the nanoparticles can effectively target solid tumors in cancer cell‐bearing mice, indicating that the solid tumor was a foundation for the enrichment of the nanoparticles by the EPR effect, which showed the important potential of biodegradable inorganic nanoparticles in clinical drugs for tumor therapy.